The phenomenon of lipid metabolism "cut" mutants - Zach, Róbert; Převorovský, Martin (Yeast (Chichester, England), 2018)
Every cell cycle iteration culminates with the resolution of a mitotic nucleus into a pair of daughter nuclei, which are distributed between the two daughter cells. In the fission yeast Schizosaccharomyces pombe, the faithful division of a mitotic nucleus depends on unperturbed lipogenesis. Upon genetically or chemically induced perturbation of lipid anabolism, S. pombe cells fail to separate the two daughter nuclei and subsequently initiate lethal cytokinesis resulting in the so-called "cut" terminal phenotype. Evidence supporting a critical role of lipid biogenesis in successful mitosis in S. pombe has been accumulating for almost two decades, but the exact mechanism explaining the reported observations had been elusive. Recently, several studies established a functional link between biosynthesis of structural phospholipids, nuclear membrane growth, and the fidelity of "closed" mitosis in S. pombe. These novel insights suggest a mechanistic explanation for the mitotic defects characteristic for some S. pombe mutants deficient in lipid anabolism and extend our knowledge of metabolic modulation within the context of the cell cycle. In this review, we cover the essential role of lipogenesis in "closed" mitosis, focusing mainly on S. pombe as a model system.
Keywords: lipogeneze; Lipogenesis; Mitosis; jaderný obal; mitóza; Schizosaccharomyces pombe; catastrophic mitosis; Nuclear Envelope; Phospholipids; cell cycle progression; fosfolipidy; Schizosaccharomyces; membránové lipidy; Membrane Lipids; fission yeast; lipid metabolism; cut phenotype